Bahasa Inggris - Hafid Al Afif; Maria Ulfa; Sri Yamtinah; Mohammad Masykuri; Bakti Mulyani; Ari Syahidul Shidiq (Postgraduate, University of Mataram, 2025)
The study conducted at SMA N Karangpandan aimed to assess the literacy abilities of class X students using the AKM instrument based on chemical science. The research employed a descriptive qualitative method with purposive sampling, involving 137 students from various class X groups. Data was collected through tests and interviews. The findings revealed that 5% of students required special intervention, 17% were in the basic literacy category, 31% demonstrated proficient literacy, and 47% exhibited advanced literacy. Those needing intervention could retrieve explicit information but struggled with proper interpretations. Students with basic literacy could find and interpret explicit information effectively, while proficient students could handle implicit information and integrate portions of it. Advanced students demonstrated the ability to integrate, evaluate, and reflect upon text. The utilization of the AKM instrument aimed to familiarize class X students with AKM questions, helping them comprehend question forms, content, and context. The study's outcomes serve as an indicator of class X students' readiness for AKM assessments, offering insights into their literacy levels and providing a basis for further educational strategies.